Designing the Ideotype Mycorrhizal Symbionts for the Production of Healthy Food - Avio, Luciano; Turrini, Alessandra; Giovannetti, Manuela; Sbrana, Cristiana (Frontiers in Plant Science, 2018)
The new paradigm in agriculture, sustainable intensification, is focusing back onto beneficial soil microorganisms, for the role played in reducing the input of chemical fertilizers and pesticides and improving plant nutrition and health. Worldwide, more and more attention is deserved to arbuscular mycorrhizal fungi (AMF), which establish symbioses with the roots of most land plants and facilitate plant nutrient uptake, by means of a large network of extraradical hyphae spreading from colonized roots to the surrounding soil and functioning as a supplementary absorbing system. AMF protect plants from biotic and abiotic stresses and are able to modulate the activity of antioxidant enzymes and the biosynthesis of secondary metabolites (phytochemicals), such as polyphenols, anthocyanins, phytoestrogens and carotenoids, that play a fundamental role in promoting human health. An increasing number of studies focused on the use of AMF symbionts for the production of functional food, with enhanced nutritional and nutraceutical value. Yet, while a large number of diverse plant species was investigated, only few AMF were utilized, thus limiting the full exploitation of their wide physiological and genetic diversity. Here, we will focus on AMF effects on the biosynthesis of plant secondary metabolites with health-promoting activity, and on the criteria for a finely tuned, targeted selection of the best performing symbionts, to be utilized as sustainable biotechnological tools for the production of safe and healthy plant foods.